DIGITAL APPROACH TO TEACH CREATIVE WRITING WITH SECONDARY STUDENT LEARNERS OF ENGLISH - Rocha, Ana Paula; Casanova, Maria Prazeres (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
In this article, we share our reflections and analysis on the potential of digital resources in teaching creative writing in English and promoting the learning of a foreign language in a collaborative environment. Our work aims to identify best practices in using digital tools such as Google Workspace, Padlet, and Issuu, for in-class activities with seventy secondary students. We conducted a study following an action-research methodology in the classroom and applied digital teaching strategies with learners of a second language. The focus was on a creative and collaborative writing process, to develop imagination in the conception of fictional stories while promoting collaborative skills. Our key question was